ANALISIS KECEMASAN MATEMATIKA (MATH ANXIETY) SELAMA PROSES PEMBELAJARAN SISWA KELAS IV SD NEGERI 113 PALEMBANG - Sepira Sari, Lidia; Jayanti, Jayanti; Tanzimah, Tanzimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the presence of math anxiety among fourth-gradestudents at SD Negeri 113 Palembang during the learning process. This anxietywas reflected in students' lack of self-confidence, feelings of fear, and difficulties inparticipating in mathematics learning. The study aimed to describe the forms of mathanxiety experienced by students and to identify the learning strategies used byteachers to overcome this anxiety. This study employed a descriptive qualitativeapproach. The research subjects were fourth-grade students at SD Negeri 113Palembang. Data were collected through questionnaires, observations, interviews,and documentation. Data were analyzed through data reduction, data display, andconclusion drawing. The findings revealed that students' math anxiety emerged intwo aspects: cognitive and affective. In the cognitive aspect, anxiety was indicatedby students' low ability to solve mathematics problems, lack of self-confidence incompleting assignments, difficulty concentrating during the learning process, andconcerns about failing to solve mathematics problems. In the affective aspect,anxiety was reflected in students' feelings of nervousness during mathematicslessons, their dislike of mathematics learning, and feelings of restlessness whensolving problems or answering questions in class. The findings also showed that theteacher's learning strategies, such as the use of instructional media (Smart TV andconcrete learning media), providing examples gradually, creating an enjoyableclassroom atmosphere, and offering support to students, helped reduce students'math anxiety.